Tinjauan Yuridis Perlindungan Hukum Bagi Pekerja Radiasi Non-PNS Dalam Pekerjaan Berisiko Radiasi di Provinsi Bali - Syarifuddin, Syarifuddin; Gede Utara Hartawan, I Gusti Agung; Dharmawan, Ni Ketut Supasti; Eka Putra, I Wayan Gede Artawan (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article aims to analyze legal arrangements related to the protection of non-civil servant radiation workers in the Province of Bali, identify legal protection gaps between civil servant and non-civil servant radiation workers, and provide recommendations to ensure proper and fair protection for all radiation workers. This study uses normative legal methods to analyze regulations on the protection of non-civil servant radiation workers. Qualitative-descriptive analysis is used to identify legal gaps and formulate recommendations based on the principles of justice. The results of the study show that the analysis of legal protection for non-civil servant radiation workers in Bali Province shows a significant gap compared to civil servants, especially in benefits, access to health facilities, and legal support. Despite the regulations, their implementation still faces challenges in monitoring and workers' awareness of their rights. Regulatory revisions, increased oversight, and equality of benefits are needed to ensure equitable protection for all radiation workers. This strategic step will create a safe work environment, respect human rights, and uphold the principle of justice without discrimination.